Pelatihan ASHAR untuk Meningkatkan Asertivitas terhadap PelecehanSeksual Santri Pesantren - Riska Sri Hayani Fitri; Fittra Tulaila; Irsawinda Nadhifa; Lidya Nengsih; Raisa Qurratu ‘Ain Fasa; Zahratul ‘Aini (Departemen Psikologi, Universitas Negeri Padang, 2024)
Sexual harassment can occur in the Islamic boarding school environment and quite a few victims show a sexy choice to remain silent considering their low ability to assertiveness. There is a need to improve assertiveness abilities through assertiveness training called ASHAR. ASHAR (Anti Sexual Harassment) training is training using psychoeducational methods in dealing with sexual understanding. The method used in this research is quantitative research with an experimental method using a one group pretest- posttest design conducted on 36 students of Islamic Boarding School X in Agam Regency. The results of this study indicate that there was an increase in assertiveness skills towards sexual understanding after ASHAR training was carried out for the students of Pondok Pesantren X in Agam Regency.